2022
DOI: 10.2196/38876
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Topics and Motivating Factors Behind Human-Social Chatbot Interactions: Thematic Analysis of User Experiences

Abstract: Background Although social chatbot usage is expected to increase as language models and artificial intelligence improve, very little is known about the dynamics of human-social chatbot interactions. Specifically, there is a paucity of research examining why human-social chatbot interactions are initiated and the topics that are discussed. Objective We sought to identify the motivating factors behind initiating contact with Replika, a popular social chat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…Previous studies have identified some dynamics of why users try to engage with conversational agents. They point out that intrinsic motivations, such as general interest in AI, have a strong positive influence on the intention to use the chatbot [32][33][34]. In this study, we have other findings besides that.…”
Section: ) Dynamicsmentioning
confidence: 49%
See 1 more Smart Citation
“…Previous studies have identified some dynamics of why users try to engage with conversational agents. They point out that intrinsic motivations, such as general interest in AI, have a strong positive influence on the intention to use the chatbot [32][33][34]. In this study, we have other findings besides that.…”
Section: ) Dynamicsmentioning
confidence: 49%
“…These social chatbots assist in completing specific tasks and foster feelings of self-disclosure among users [31]. Recent studies [32][33][34] reveal that a blend of intrinsic curiosity about AI and practical needs for efficiency and support drives user engagement with chatbots. Effective chatbot design requires addressing both technological capabilities and diverse user motivations.…”
Section: Chatbot As Partners In Learning and Well-being Supportmentioning
confidence: 99%